Critical Thinking Session (CTS) - Nor Hayati, Jaya; Nur Rasfina, Mahyan; Nor Amalina, Ahmad; Dzetty Soraya, Abdul Aziz (UNIMAS Publisher, 2023)
CTS in Physics course provides quantitative and analytic skills needed for analysing data and solving problems in the sciences area. It involves crafting a learning environment where students can explore on their own and understand how the physical world works, and to connect complex scientific concepts to their daily lives. This activity requires students to work as a team.